The Mediterranean Variety of Capitalism, Flexibility of Work Schedules, and Labour Productivity in Southern Europe - Vallejo-Peña, Alberto; Giachi, Sandro (REGION, 2018)
Sociology has long been used to highlight the existence of diverse institutional models between geographical areas of Europe in terms of work organisation. Based on this, we propose to compare the situation of four representative countries of southern Europe (Spain, Italy, Greece and Portugal) with that of the rest of Europe, by addressing the number of hours worked and the flexibility of working hours as key elements of their institutional model of work organisation, as well as their impact on levels of labour productivity. Taking the model of the varieties of capitalism as a reference, this study compares the behaviour of the Mediterranean (southern) countries with other European regions. Indicators have been obtained from the 2010 and 2015 waves of the European Work Conditions Survey (EWCS) that include the number of hours worked, the flexibility in the hours of entry and exit, and the tendency to work the same number of hours per day. After comparing averages in both waves and applying linear regressions, the following conclusions have been reached: (1) Productivity in southern countries is on a par with the European average but far from the more corporatist and liberal (northern) areas; (2) the South maintains a high average of hours worked (above the European average) to compensate for the poor productivity of its hours; and (3) the incorporation of flexible schedules is associated with elevated levels of productivity.